Respiratory symptons prevalence among traffic policemen in Malaysia - Mohamad Jamil, Putri Anis Syahira; Karuppiah, Karmegam; Rasdi, Irniza; Mohd Tamrin, Shamsul Bahri; Sambasivam, Sivasankar; Mohammad Yusof, Nur Athirah Diyana; Azmi, Ihtifazuddeen (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Traffic policemen are exposed to polluted air for a long time in high concentrations since they are working outside for most of the time which is bad for their health. Hence, this study was to determine the prevalence of respiratory symptoms and pulmonary function among traffic police in Kuala Lumpur and Johor Bahru. Methods: A pulmonary function test using spirometer was used to measure the pulmonary function of subjects. A questionnaire on respiratory symptoms translated version from IUALTD was used. The questionnaire includes background data, occupational and health history. Results: The traffic policemen were determined as having lower lung function parameters; low FVC% predicted (89.6%) and low FEV1% predicted (94%) due to their nature of work and the environment. Coughing was present at the highest (33.6%) among them, whereas wheezing was found the least (15.7%) of the workers. Conclusions: Findings from this study, indicated that there is a development of respiratory diseases and deterioration of lung function among traffic policemen. These baseline data can serve as a reference to the top management of traffic police officers in order to develop an occupational safety and health guideline for police officers as they are not covered by Occupational Safety and Health Act (OSHA, Act 514 1994).